2020
DOI: 10.2147/phmt.s252061
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Intestinal Parasitic Infection and Its Associated Factors Among School Children in Two Primary Schools in Harbu Town, North East Ethiopia: Cross-Sectional Study</p>

Abstract: Background: Intestinal parasitic infections (IPIs) are major health problems in many developing countries. School children between the ages of 5 and 15 years suffer the highest infection rate and parasitic burden that are attributed to poor sanitation and hygiene. In Ethiopia, the prevalence of IPIs among school children is high (ranging from 66.7% to 83.8%). Methods: School-based cross-sectional study was conducted in two primary schools at Harbu Town, Northeast Ethiopia from February to May, 2018. Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
2
13
3
Order By: Relevance
“…Entamoeba histolytica was the most prevalent parasite in our study (29.2%), which is consistent with a study conducted in Harbu Town, Ethiopia [ 17 ], whereas another study in children in central Albania found that Entamoeba histolytica was the least prevalent (0.3%) [ 33 ]. These discrepancies might be due to variations in school WASH programs between schools in our study and in Albania.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Entamoeba histolytica was the most prevalent parasite in our study (29.2%), which is consistent with a study conducted in Harbu Town, Ethiopia [ 17 ], whereas another study in children in central Albania found that Entamoeba histolytica was the least prevalent (0.3%) [ 33 ]. These discrepancies might be due to variations in school WASH programs between schools in our study and in Albania.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a study among Debre Elias Primary School in Amhara Regional State, Ethiopia, reported an intestinal parasitosis rate in school children of 84.3%, with dual infections of 14.2% and high infection rates for hookworm (71.2%), Entamoeba histolytica (6.7%) and Strongyloides stercoralis (2.4%) [ 16 ]. Another study in two primary schools at Harbu town, south Wollo zone revealed the overall prevalence of intestinal parasitosis was 21.5% [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was in agreement with the study done by Abossie and Seid, 33 and Khadka et al 34 reported that the prevalence of parasitic infection was higher in girls than in boys regardless of significant association. But this in contrast to a study done by Gebretsadik et al 35 This is most likely to be influenced by cultural values that parents who give more priorities to the health of their sons than their daughters and females may come into contact with more contaminated water and food than males, which may increase the risk of exposure to parasites.…”
Section: Discussioncontrasting
confidence: 57%